High temperature electronics in Europe - Johnston, C (2006)
High temperature electronics (HTE) has been a European research theme since HITEN, the High Temperature Electronics Network of Excellence was established in 1990. This paper reviews passed and current pan European projects in HTE and seeks to demonstrate that HITEN has been pivotal in helping establish a commercial landscape for exploitation of HTE in the key market sectors of oil and gas, aerospace and automotive. A number of HTE projects will be reviewed and the commercialisation strategy for Europe discussed. Copyright © 2006 International Microelectronics And Packaging Society.